Semantics of the terms of the human body in Quechua: metaphor, metonymy and conceptual interaction - Domínguez Chenguayen, Frank Joseph (2022)
In Ayacucho-Chanca Quechua, corporeal terms evoke different domains or conceptual frameworks. The objective is to clarify the nature of the polysemic behavior of these corporeal terms. Theoretically, it starts from a set of principles that govern the phenomenon of polysemy within the framework of cognitive linguistics. Methodologically, the data has been obtained from an elicitation process. The results allow reaffirming the metaphor and metonymy as necessary procedures, but (at the same time) insufficient to explain the generation of new meanings. The explanation also requires an interactional process.